Spatial Analysis of Risk Factors for Tuberculosis Incidence in South Jakarta City in 2022 - Syarifah Khodijah; Artha Prabawa (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: South Jakarta City, within DKI Jakarta, bears a substantial burden of TB cases, yet case detection rates and treatment success remain low. Factors such as population density, gender disparity, socio-economic conditions, and healthcare accessibility influence TB transmission. The city's high population density presents challenges in controlling TB spread. Additionally, males and low-income families face higher TB risks. Objective: This study aims to analyze TB case distribution across 10 districts in South Jakarta, assess TB case clustering, and understand the spatial regression model of TB risk factors. Method: The methodology of this research utilizes a quantitative approach with an ecological study design and spatial methodology, secondary data from various sources, including the national TB control reporting application. Data processing involves GeoDa v1.22, QGIS v.3.32.3, SPSS v.22, and GWR v4.0 applications for spatial analysis. Result: Findings reveal that spatial autocorrelation tests using Moran's Index on TB cases in South Jakarta City are not statistically significant, indicating no spatial autocorrelation. The LISA test identifies Mampang Prapatan District as a cold spot in Quadrant III (Low-Low). GWR regression analysis highlights three spatially influential risk factor variables affecting TB cases: gender ratio, number of health centers, and population density. The first two variables affect all districts in South Jakarta City, whereas population density only impacts the Setiabudi District. Conclusion: In conclusion, Mampang Prapatan district in South Jakarta City exhibits low TB transmission risk, considering population density and other factors. Notably, three spatial risk factors affect TB transmission in South Jakarta City, warranting attention from the health department in TB elimination efforts.